Different outcomes for the MYB floral symmetry genes DIVARICATA and RADIALIS during the evolution of derived actinomorphy in Plantago. Issue 2 (27th January 2014) - Reardon, Wesley; Gallagher, Pauline; Nolan, Katie M.; Wright, Hayley; Cardeñosa‐Rubio, Maria Cruz; Bragalini, Claudia; Lee, Chui‐Sang; Fitzpatrick, David A.; Corcoran, Killian; Wolff, Kirsten; Nugent, Jacqueline M.
Summary The gene network that specifies flower shape in Antirrhinum majus (bilateral floral symmetry or zygomorphy) includes two MYB‐class genes – RADIALIS (RAD) and DIVARICATA (DIV). RAD is involved in establishing the dorsal identity program and its role is to regulate the domain of activity of DIV (the ventral identity program) by restricting it to ventral regions of the flower. Plantago is in the same family as Antirrhinum but has small, radially symmetrical (actinomorphic) flowers derived from a zygomorphic ancestral state. Here we investigate the MYB‐class floral symmetry genes and the role they have played in the evolution of derived actinomorphy in Plantago lanceolata. A DIV ortholog (PlDIV) but no RAD ortholog was identified in P. lanceolata. PlDIV is expressed across all petals and stamens later in flower development, which is consistent with the loss of RAD gene function. PlDIV expression in anther sporogenous tissue also suggests that PlDIV was co‐opted to regulate cell proliferation during the early stages of pollen development. These results indicate that evolution of derived actinomorphy in Plantago involved complete loss of dorsal gene function, resulting in expansion of the domain of expression of the ventral class of floral symmetry genes.